2022
DOI: 10.3389/fimmu.2022.1042741
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal immune profiling after radiation-attenuated sporozoite vaccination reveals coordinated immune processes correlated with malaria protection

Abstract: BackgroundIdentifying immune processes required for liver-stage sterilizing immunity to malaria remains an open problem. The IMRAS trial comprised 5x immunizations with radiation-attenuated sporozoites resulting in 55% protection from subsequent challenge.MethodsTo identify correlates of vaccination and protection, we performed detailed systems immunology longitudinal profiling of the entire trial time course including whole blood transcriptomics, detailed PBMC cell phenotyping and serum antigen array profilin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Previous studies have reported on the whole blood transcriptional response after immunization with irradiated SPZ ( Pf SPZ). 24 , 26 To potentially increase the resolution of the analysis, we focused our analysis of the transcriptional response on antigen-specific cells by stimulating cells in vitro with NF54 Pf- SPZ or media control and then magnetically enriching for CD69 + cells, an activation marker that can be used as surrogate marker for antigen-specific cells. 27 After quality control and filtering out lowly expressed genes, 15,923 genes survived for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported on the whole blood transcriptional response after immunization with irradiated SPZ ( Pf SPZ). 24 , 26 To potentially increase the resolution of the analysis, we focused our analysis of the transcriptional response on antigen-specific cells by stimulating cells in vitro with NF54 Pf- SPZ or media control and then magnetically enriching for CD69 + cells, an activation marker that can be used as surrogate marker for antigen-specific cells. 27 After quality control and filtering out lowly expressed genes, 15,923 genes survived for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Similar analyses have been done following the five successive immunization sessions, and the transcriptome responses to RAS differed strongly after each immunization. 26 Notably, as opposed to the first immunization session, the subsequent four immunizations revealed a positive correlation between IFN-associated gene transcription and protection. Nevertheless, the authors described that the biggest factor driving variability in transcriptome and circulating cell phenotype populations was inter-subject variability.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…CHMI could help better understand naturally acquired immunity as well as the development of protective immunity. Indeed, immunization studies of chemically attenuated whole PfSPZ vaccine and radiation‐attenuated sporozoite vaccination 16 revealed induced overall proportion of CD3 + γδ T cells, especially Vγ9Vδ2 T cells 17–19 . CHMI after irradiation‐attenuated PfSPZ vaccination in previously malaria‐exposed population expanded Vδ1 + and Vδ1 − Vδ2 − T cells with multiple clonotypes during blood‐stage Plasmodium infection 20 .…”
Section: γδ T Cells In Response To Plasmodium Sporozoite Vaccination:...mentioning
confidence: 99%
“…To date, however, the protective antigen repertoire has not been identified, motivating an ongoing effort to use reagents from individuals immunized with PfSPZ for antigen discovery [ 50 , 63 , 64 ]. The role of γδ T cells, particularly the Vδ2 subset [ 4 , 65 69 ], and of NK cells [ 70 , 71 ] in the induction of protective immunity by PfSPZ vaccines are important areas of ongoing investigation. A reappraisal of the role of antibodies is also underway [ 72 74 ], with the tools of systems serology offering an innovative approach to elucidate antibody-associated protective mechanisms following SPZ immunization [ 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%